2022
DOI: 10.1002/jgc4.1554
|View full text |Cite
|
Sign up to set email alerts
|

Application of motivational interviewing strategies with the extended parallel process model to improve risk communication for parents of children with familial hypercholesterolemia

Abstract: Current genetic counseling practice has not been found to significantly increase risk communication between family members. A more diverse set of genetic counseling approaches may be needed. A genetic counseling intervention based on motivational interviewing principles and the extended parallel process model was utilized to increase cascade outcomes within families with familial hypercholesterolemia, a common, underdiagnosed, and treatable condition. Parents of children with familial hypercholesterolemia were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Incorporating standardized simulations for summative evaluation in GC programs could allow for assessment consistency in competency-based student evaluation and potentially be a means of demonstrating competence to obtain certification. et al, 2006), motivational interviewing (Winchester et al, 2022), appropriate psychological counseling and literacy levels training (Riddle et al, 2021), an evidence-based psychotherapeutically oriented counseling approach (Austin, 2020), and patient-centered communication skills (Lowe et al, 2023). The communication and counseling-related skills taught in studies such as those may be the most ideal targets for the development of simulation-based assessments of entry-level GC competence.…”
Section: A Ss E Ss Ing Coun S Eling S K Ill Smentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating standardized simulations for summative evaluation in GC programs could allow for assessment consistency in competency-based student evaluation and potentially be a means of demonstrating competence to obtain certification. et al, 2006), motivational interviewing (Winchester et al, 2022), appropriate psychological counseling and literacy levels training (Riddle et al, 2021), an evidence-based psychotherapeutically oriented counseling approach (Austin, 2020), and patient-centered communication skills (Lowe et al, 2023). The communication and counseling-related skills taught in studies such as those may be the most ideal targets for the development of simulation-based assessments of entry-level GC competence.…”
Section: A Ss E Ss Ing Coun S Eling S K Ill Smentioning
confidence: 99%
“…Programs should use tools that promote and evaluate counseling competencies, and which do not suppress individual styles or viewpoints. Although more work needs to be done to investigate best pedagogical approaches for counseling skills in genetic counseling, studies have shown beneficial effects in the areas of tailoring communication through video‐supported feedback (Pieterse et al., 2006), motivational interviewing (Winchester et al., 2022), appropriate psychological counseling and literacy levels training (Riddle et al., 2021), an evidence‐based psychotherapeutically oriented counseling approach (Austin, 2020), and patient‐centered communication skills (Lowe et al., 2023). The communication and counseling‐related skills taught in studies such as those may be the most ideal targets for the development of simulation‐based assessments of entry‐level GC competence.…”
Section: Assessing Counseling Skillsmentioning
confidence: 99%
“…Change, while more commonly thought of in terms of reducing a risk behavior like substance misuse or adding a protective behavior such as physical activity, could also apply to undergoing genetic testing. There has been some conceptual work discussing the role of MI for GC (Ash, 2017) and some qualitative and pilot studies in the GC realm, largely focused on familial hypercholesterolemia and cancer (de Geus et al, 2016;Kinney et al, 2014;Kruger et al, 2019;Razo-Mejia et al, 2014;Resta et al, 2006;Schwartz et al, 2014;Winchester et al, 2022). In MI much of the psychologic work, that is, problem-solving and action planning is done by the patient.…”
Section: Defining Motivational Interviewing (Mi)mentioning
confidence: 99%
“…More recently, there has been increased discussion regarding a potential role for incorporating more persuasion or directionality within GC, around both proband testing as well as family communication and cascade testing (Ash, 2017; de Geus et al, 2016; Kinney et al, 2018; Kruger et al, 2019; Winchester et al, 2022). The rationale for “persuasive GC” is based on the premise that some genetic tests provide actionable information that would clearly benefit patients and families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation